2013
DOI: 10.1086/671258
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Explicit Conditions for Waterborne Pathogen Invasion

Abstract: Waterborne pathogens cause many possibly lethal human diseases. We derive the condition for pathogen invasion and subsequent disease outbreak in a territory with specific, space-inhomogeneous characteristics (hydrological, ecological, demographic, and epidemiological). The criterion relies on a spatially explicit model accounting for the density of susceptible and infected individuals and the pathogen concentration in a network of communities linked by human mobility and the water system. Pathogen invasion req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 73 publications
2
42
0
Order By: Relevance
“…Although controlling contamination and proliferation of potential pathogens in freshwater is extremely challenging (Cabral, 2010), their control could be achieved partly at the level of the host, such as by infection tracking in human populations. For example, Gatto et al (2013) observed that hydrological network, human mobility, and landscape complexity mediate the spread of diarrheal infections from Vibrio cholera that could be potentially modeled to predict which communities will be hit hardest during the epidemic.…”
Section: Aquatic Microbial Communities and Host Susceptibilitymentioning
confidence: 99%
“…Although controlling contamination and proliferation of potential pathogens in freshwater is extremely challenging (Cabral, 2010), their control could be achieved partly at the level of the host, such as by infection tracking in human populations. For example, Gatto et al (2013) observed that hydrological network, human mobility, and landscape complexity mediate the spread of diarrheal infections from Vibrio cholera that could be potentially modeled to predict which communities will be hit hardest during the epidemic.…”
Section: Aquatic Microbial Communities and Host Susceptibilitymentioning
confidence: 99%
“…Developments and applications of OCNs have appeared recently. For example, OCN arrangements have been used to design laboratory experiments with protist metacommunities where patches (true living ecosystems) are arranged in optimal network shapes to simulate the type of directional biological dispersal one expects in fluvial environments (47,48), or used in spatially explicit models of epidemics of waterborne disease where river networks act as ecological corridors for pathogens (49). The OCN concept of feasible optimality has inspired a number of studies on fractal structures in nature not necessarily related to true equilibrium properties of the system, e.g., a class of nonequilibrium interfaces in random exchanges Ising ferromagnets (50).…”
Section: Complexitymentioning
confidence: 99%
“…We argue that spatially disconnected models cannot directly account for the spatial mechanisms of pathogen dissemination (i.e. hydrological transport and human mobility), which play a crucial role in the initial phase of the outbreak, when the infection starts propagating into disease-free regions [13,48]. Conversely, spatial coupling may become less important when looking at longer time horizons, once the epidemic has already spread all across the country.…”
Section: Discussionmentioning
confidence: 94%